Dampak Pengambilan Keputusan terhadap Partisipasi Masyarakat dalam Pembangunan Desa Menuju Keberlanjutan Program di Desa Mendana Raya - Syahdan; Rodi Aswandi; Herman; Bahraen Rinaldi; Ahmad Jalaluddin (Pendidikan Al-Gafari, 2024)
Development planning is a form of planning related to efforts to increase economic growth and community welfare. Indonesia is a developing country that is inseparable from the development planning program. This study aims to determine Community Participation in Village Development Decision Making for the Sustainability of Programs in the Village. The type of this research is descriptive qualitative which seeks to explain or describe a condition, event, or object such as a person, or anything related to the research. Analysis of data obtained based on field data, in the analysis process has four stages, namely reducing, triangulating, presenting data, and verifying/conclusions. Based on research conducted through interviews, observations, and documentation Forms of community participation in a Program: (a) Community participation in the planning process, in this case, the community participates in the planning process but does not participate actively. (b) In this case, the community participates actively in the program implementation process. The program activity implementation in Mendana Raya Village is carried out by the community with self-reliance and supported by village officials such as the head of RT, RW, the Program Activity Management Team, and the Village Head. Factors that influence community participation in a program in Mendana Raya Village are factors such as the ability, willingness, and opportunity of the community, where the community is aware that they need to participate in a program so that the program can run well so that it can make Mendana Raya Village even better, which has an impact on helping to smooth the daily lives of the community.